Crowding in private quality: The equilibrium effects of public spending in education - Andrabi, Tahir; Bau, Natalie; Das, Jishnu; Karachiwalla, Naureen; Khwaja, Asim Ijaz (Oxford University Press, 2024)
We estimate the equilibrium effects of a public school grant program administered through school councils in Pakistani villages with multiple public and private schools and clearly defined catchment boundaries. The program was randomized at the village level, allowing us to estimate its causal impact on the market. Four years after the start of the program, test scores were 0.2 standard deviations higher in public schools. We find evidence of an education multiplier: test scores in private schools were also 0.2 standard deviations higher in treated markets. Consistent with standard models of product differentiation, the education multiplier is greater for those private schools that faced a greater threat to their market power. Accounting for private sector responses increases the program’s cost-effectiveness by 85% and affects how a policy maker would target spending. Given that markets with several public and private schools are now pervasive in low- and middle-income countries, prudent policy requires us to account for private sector responses to public policy, both in policies’ design and evaluation.